(untitled) (مجلة إحالات, 2026)
This paper addresses the issue of translation in the Algerian novel. The traditional approach to translation: the transfer of a text from one language into another calls for a profound reflection on translation when it operates within the same cultural space characterized by a plurality of languages (Maghrebi Arabic /north African Arabic, standard Arabic, Berber, French, ect.). The question is to what extent it is possible to identify the limits and boundaries between languages in the Algerian literary field. In this regard, we attempt to propose some avenues of reflection for the Algerian text, focusing / with an emphasis on the "poetics" and the philosophy of "Relation" in Edouard Glissant’s work, so as to capture the aspects of translating in the act of writing.